Investigation of the cytotoxic effect of Lallemantia Fisch. & C.A. Mey. species growing in Türkiye on various cancer cell lines - Çelik, Ali Kaya; Sancar, Pelin Yılmaz; Taskin, Irmak Icen; Kurşat, Murat (My University, 2024)
The genus Lallemantia (Lamiaceae) is popularly known as \"Dragonhead\". The genus, which has been proven to have extremely rich compounds, is used in the treatment of many diseases among the people. The genus is represented by 5 taxa in the world and 3 taxa are naturally distributed in Türkiye. In this study, the cytotoxic properties of methanolic extracts of the above-ground parts of Lallemantia peltata, Lallemantia iberica and Lallemantia canescens taxa were investigated against BEAS-2B, SH-SY5Y, HCT 116 and Hep G2 cell lines. Changes in the viability of cancer cells were determined using the MTT method. The results showed that all three species had varying degrees of cytotoxic effect. This effect was maximum in L. canescens with 53.54% (p<0.001) on HCT 116, 37.53% (p=0.005) on SH-SY5Y and 32.03% (p=0.026) on Hep G2 at 800 ?g/ml and minimum in L. iberica. In addition, the herbal extracts had no toxic effect on healthy lung cells (BEAS-2B).
Keywords: Lallemantia; SH-SY5Y; Hep G2; Cytotoxic; BEAS-2B; HCT 116